The Limits of Sanity: Visions of Stigma in Mental Health Narrative - Piquer Vidal, Adolf (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
Literature reproduced a social stereotype described as "mad". In the classical world we found the image of Orestes, affected by mania. Under this term, Don Quixote is presented to the eyes of those who observe and read him. The use of qualifiers and descriptions that the narrator uses in the book serves to illustrate a traditional vision of madness in literature, often under a prism of stigma, as Goffman considers it, because of its perception and social information (1970: 57). The quixotic mad person corelates with the conception of madness in 17th century.Its visibility, however, is diverse: from hiding and seclusion, in contrast to public display and scorn, there are a number of social nuances that could be considered (Goffman 1970: 63). We analyze several novels in which the vision of neurodivergence presents a perspective that changes through time, and in which the role of the narrator can give us clues to ideological issues.
Keywords: Novel; Madness; Literature and society